PELESTARIAN TINGGALAN BUDAYA BAWAH AIR: PEMANFAATAN KAPAL KARAM SEBAGAI DAYA TARIK WISATA SELAM - Roby Ardiwidjaja (Badan Riset dan Inovasi Nasional, 2017)
Abstract. Preservation of Underwater Cultural Heritage: Shipwreck as a Diving Attraction. Indonesia is the largest archipelago country in the world; two thirds of its territory is the sea. One of President Jokowi's missions is that the government will focus more on Indonesian maritime strategic thinking, by implementing the concept of